Early experience with a helical coronary thrombectomy device in patients with acute coronary thrombosis. Issue 5 (1st May 2002) - Constantinides, S; Lo, T S N; Been, M; Shiu, M F
Abstract : Objective: To report our experience with a new thrombectomy device (X-SIZER TM ) in patients with angiographically visible thrombus or total coronary occlusion in the setting of acute coronary syndromes. Design: A safety and feasibility study in the use of the X-SIZER during intervention in patients with acute coronary syndromes. Patients: 35 patients, age range 31 to 83 years (mean 60). Setting: University Hospitals of Coventry and Warwickshire NHS Trust (tertiary referral centre). Interventions: The indication for intervention was primary or salvage percutaneous coronary intervention for acute myocardial infarction in 17 of the 35 patients; unstable angina or non-ST-elevation myocardial infarction in 10; and unstable postinfarct angina in eight. Abciximab was given in 11 patients. Main outcome measures: Device success (successful deployment of the device at the site of the lesion with resultant improvement in TIMI flow); clinical success (no residual stenosis at the end of the procedure with no in-hospital major adverse coronary events). Results: Successful use of the device was achieved in 26 of the 35 cases. It failed to cross the lesion in five and failed to improve TIMI flow despite crossing the lesion in four. Clinical success was achieved in 30 of the 35 cases. Device related complications occurred in two cases (vessel perforation) and there was one intraprocedural death (acute myocardial infarction with cardiogenic shock). Conclusions: Thrombectomy with the X-SIZER catheter system appears promising in percutaneous coronary intervention where thrombus extraction is considered necessary before stent implantation.